SHIP ARREST IN INDONESIA AND CROSS-BORDER MARITIME DISPUTE - Indrawan, Immanuel A. (Indonesian Journal of International Law, 2017)
Ship arrest is an in rem action on ships that exercised with purpose of obtaining security for maritime claims. The arrest is intended to prevent a ship from moving pending settlement of the claim and consequently will also prevent her owners from enjoying any profits. In present shipping industry, which became more borderless, dispute involving different nationals and jurisdictions might arise. In such case, existence of clear and certain rules are one of the keys to resolve them. In respect of that, ship arrest has been introduced in Indonesia through the Law number 17 Year 2008 “Shipping Law”. Since the enactment of Shipping Law, ship arrest is possible to carried out within the Indonesian jurisdiction. However, the practice of ship arrest in Indonesia is relatively new comparing to other countries such as Netherlands and Singapore, which have implemented it long before Indonesia. Another question is whether it is necessary for Indonesia to be a party in international treaties on arrest of ships. Learned from examples outside Indonesia, we may able to see issues concerning ship arrest in Indonesia; existence of the implementing rules, compatibility with the current civil procedural rules, readiness of the courts to implement it, etc. Responding to the development of shipping industry, Indonesia must assured to moving onward by showing its readiness in following international practice on shipping law. This readiness is also an indicator of seriousness in manifesting the idea of making Indonesia as an axis of world maritime.